Proceedings of the 28th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Softw 2020
DOI: 10.1145/3368089.3417934
|View full text |Cite
|
Sign up to set email alerts
|

WebJShrink: a web service for debloating Java bytecode

Abstract: As software projects grow in complexity, they come packaged with under-utilized libraries and therefore become bloated. Though several software debloating tools exist, none of them help developers gain insights into how under-utilized those libraries are nor help developers build conidence in the behavior preservation of software after debloating. To bridge this gap, we developed WebJShrink, a visual analytics tool for analyzing and pruning bloated software projects. WebJShrink is built on JShrink which uses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Instead of removing redundant bytecode in each artifact, we can notify developers to refactor when the usage of an artifact is relatively low. Additionally, the authors make use of this tool as a backend of WebJShrink, a visualization interface allowing developers to select removal options [15].…”
Section: A Dependency Analysis Toolsmentioning
confidence: 99%
“…Instead of removing redundant bytecode in each artifact, we can notify developers to refactor when the usage of an artifact is relatively low. Additionally, the authors make use of this tool as a backend of WebJShrink, a visualization interface allowing developers to select removal options [15].…”
Section: A Dependency Analysis Toolsmentioning
confidence: 99%
“…Similarly, we observed that the number of bloated dependencies tends to grow over time, whether or not there is a need for it. In the last years, there is a recent resurgence of interest in debloating Java bytecode [5,14,20,28,29]. These tools remove Java bytecode using static and dynamic analysis.…”
Section: Related Workmentioning
confidence: 99%
“…We make publicly available the JShrink source code and additional resources necessary to replicate our results at https://doi.org/10.6084/m9.figshare.12435542. As a companion piece to this work, we have prototyped JShrink as an entirely online SaaS, which we call WebJShrink [41]. WebJShrink provides a rich graphical user interface for the functionality described in this paper.…”
Section: • We Demonstrate the Necessity Of Handling Dynamic Featuresmentioning
confidence: 99%